2020
DOI: 10.1055/s-0040-1716721
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Anticoagulation Delays Death in COVID-19 Patients: Cross-Sectional Analysis of a Prospective Cohort

Abstract: A hypercoagulable state has been described in coronavirus disease 2019 (COVID-19) patients. Others have reported a survival advantage with prophylactic anticoagulation (pAC) and therapeutic anticoagulation (tAC), but these retrospective analyses have important limitations such as confounding by indication. We studied the impact of tAC and pAC compared with no anticoagulation (AC) on time to death in COVID-19. We performed a cross-sectional analysis of 127 deceased COVID-19 patients and compared time to death i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A small number of retrospective studies have observed that thromboprophylactic‐dose anticoagulation is associated with improved outcomes in patients with COVID‐19, but a growing body of evidence suggests a possible advantage with using more intense regimens. Our group found a dose‐ and duration‐dependent delay in death in a cohort of 127 deceased patients with severe COVID‐19 12 . Others have also explored the effect of AC in a large cohort of hospitalized COVID‐19 patients and found superior outcomes for those treated with tAC, but the comparison group consisted of patients who either received pAC or no AC, and no conclusions could be reached regarding optimal dosing 13 .…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…A small number of retrospective studies have observed that thromboprophylactic‐dose anticoagulation is associated with improved outcomes in patients with COVID‐19, but a growing body of evidence suggests a possible advantage with using more intense regimens. Our group found a dose‐ and duration‐dependent delay in death in a cohort of 127 deceased patients with severe COVID‐19 12 . Others have also explored the effect of AC in a large cohort of hospitalized COVID‐19 patients and found superior outcomes for those treated with tAC, but the comparison group consisted of patients who either received pAC or no AC, and no conclusions could be reached regarding optimal dosing 13 .…”
Section: Introductionmentioning
confidence: 70%
“…For the remainder of the population, AC was likely withheld because of active or potential bleeding complications, low baseline hemoglobin or platelet count, and individual physician practice patterns. The precise indication for the initiation of tAC was not available for analysis, but certain observations suggest that COVID‐19‐associated hypercoagulability was a frequent indication: (a) the number of patients who continued oral anticoagulant therapy inpatient was relatively small (25.7%) corresponding to a low prevalence of pre‐existing comorbid conditions requiring AC; (b) the true inpatient incidence of VTE was unknown due to limitation of diagnostic imaging in an effort to decrease exposure and, as such, these were less likely to constitute AC indications; (c) among deceased patients in our institution, COVID‐19‐associated hypercoagulability was the sole indication in 55% of subjects 12 ; and (d) institutional guidelines recommended use of tAC in a sicker patient population.…”
Section: Discussionmentioning
confidence: 95%
“…Because of the high risk of thromboembolic complications and heparin's unique pharmacology demonstrating a reduction in both inflammation and coagulation markers in COVID-19, heparins are being studied for additional clinical endpoints of reduction in hospitalizations, progression to non-invasive mechanical ventilation, as well as mortality. Some, but not all, recently reported retrospective cohort studies, suggest an in-hospital mortality benefit for both UFH and LMWH administered at both prophylaxis and therapeutic treatment doses, especially in patients with more severe COVID-19 as evidenced by elevated D-dimer or need for mechanical ventilation [ 76 , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] ] (Summarized in Table 2 ).…”
Section: Clinical Trials Of Heparins For Prophylaxis Of Venous Thrombmentioning
confidence: 99%
“…Lower rates of intubation with both therapeutic and prophylactic anticoagulation compared to no anticoagulation On-treatment bleeding: Therapeutic anticoagulation 3%, Prophylactic anticoagulation 1.7%, No anticoagulation 1.9% USA/Ionescu F et al. [101] 127 (75 ICU) Patients who expired from COVID-19 complications Hospitalized COVID-19 Therapeutic anticoagulation (N=67) No therapeutic anticoagulation (N=60) Therapeutic anticoagulation with UFH 87% (adjusted by aPTT) or enoxaparin 3% (either 1.5 mg/kg subcutaneous once daily or 1 mg/kg twice daily (or adjusted to 1 mg/kg once daily for CrCl) or oral therapeutic anticoagulation with warfarin (3%), apixaban or rivaroxaban (combined 7%) Prophylactic anticoagulation (N=47) (37%) with subcutaneous UFH 5000 units either twice daily or three times daily or enoxaparin either 30 mg or 40 mg subcutaneous once daily No anticoagulation (N=13) (10%) Therapeutic anticoagulation initiated median day 6 Hospital protocol defined duration of anticoagulation as 5 days unless a clear indication or treating clinician choses to continue Median duration of therapeutic anticoagulation 5 days Median time to death all patients = 9 days Multivariate Cox proportional hazards model: Therapeutic anticoagulation (HR=0.15; 95% CI 0.07-0.32) and prophylactic anticoagulation (HR=0.29; 95% CI 0.15-0.58) independent predictors of longer time to death Later initiation of therapeutic anticoagulation day 3 and beyond provided greater benefit compared to earlier initiation (days 1-2) No interaction between therapeutic anticoagulation and D-dimer Any bleeding: Therapeutic anticoagulation 19% versus No therapeutic anticoagulation 19% (p=0.877) ISTH Major Bleeding: Therapeutic anticoagulation 3% versus 8% (p=0.18) Italy/Desai A et al. 575 Admitted to the emergency department and diagnosed with COVID-19 LMWH initiated in the emergency department (N=240, 42.6%) type and dose not specified NA NA Multivariate logistic regression: use of LMWH in the emergency department was associated with 60% reduction in mortality (OR 0.4; 95% CI 0.2-0.6) NA Italy/Albani 1403 Hospitalized with COVID-19 Enoxaparin at some time during hospitalization N=799 (57%) versus no enoxaparin N=604 (43%) Therapeutic enoxaparin (dose > 40 mg) N=312) Prophylactic dose enoxaparin (dose ≤ 40 mg) N=487 Median dose 40 mg [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53]...…”
Section: Clinical Trials Of Heparins For Prophylaxis Of Venous Thrombmentioning
confidence: 99%
“…LMWH usually also is used to prevent thrombosis [ 12 ]. In an observational cross-sectional prospective study by Ionescu et al, therapeutic anticoagulation was found to have better efficacy in preventing thrombotic episodes in severe COVID-19, leading to a decrease in mortality [ 13 ]. Similarly, Nadkarni and Lala, in a retrospective observational study of 4389 elderly individuals confirmed to be COVID-19-positive, evaluated the role of anticoagulation in decreasing mortality and intubation in hospitalized patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%